An ultrasensitive self-driven broadband photodetector based on a 2D-WS2/GaAs type-II Zener heterojunction. Issue 7 (6th February 2020) - Jia, Cheng; Huang, Xiaowen; Wu, Di; Tian, Yongzhi; Guo, Jiawen; Zhao, Zhihui; Shi, Zhifeng; Tian, Yongtao; Jie, Jiansheng; Li, Xinjian
Abstract : A self-driven photodetector based on WS2 /GaAs type-II Zener heterojunction is fabricated, which shows a broadband response spectrum from 200 to 1550 nm beyond the limitation of the bandgaps with a high responsivity and specific detectivity. Abstract : High-performance broadband photodetectors have attracted extensive research interest because of their significance in optoelectronic applications. In this study, a highly sensitive room-temperature (RT) broadband photodetector composed of a WS2 /GaAs type-II van der Waals heterojunction was demonstrated, which exhibited obvious photoresponse to broadband light illumination from 200 to 1550 nm beyond the limitation of the bandgaps. Impressive device performances were achieved in terms of a low noise current of ∼59.7 pA, a high responsivity up to 527 mA W −1, an ultrahigh I light / I dark ratio of 10 7, a large specific detectivity of 1.03 × 10 14 Jones, a minimum detection light intensity of 17 nW cm −2 and an external quantum efficiency (EQE) up to 80%. Transient photoresponse measurements revealed that the present detector is capable of working at a high frequency with a 3 dB cutoff frequency up to 10 kHz and a corresponding rise/fall time of 21.8/49.6 μs. Notably, this heterojunction device demonstrated Zener tunneling behaviors with a threshold voltage of −4 V. The capacitance–voltage ( C – V ) properties of the heterojunction were investigated to understand the device performances. In addition, the as-fabricated device can function as an image sensor with an outstanding imaging capability. Considering the above superior features, the proposed WS2 /GaAs type-II van der Waals heterojunction may find great potential in high-performance broadband photodetection applications.